ACUTE MYOCARDIAL INFARCTION: CAUSES, SYMPTOMS, DIAGNOSIS, AND TREATMENT (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Acute myocardial infarction (AMI), commonly known as a heart attack, is one of the most critical cardiovascular events. It occurs when blood flow to a part of the heart muscle is blocked, leading to tissue damage due to lack of oxygen. Understanding its causes, symptoms, diagnosis, and treatment options is essential for improving outcomes and reducing mortality.